2018
DOI: 10.21608/ajnsa.2018.12403
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Lactic Acid Bacteria by Gamma Radiation to Inhibit Antibiotic Resistance of some Salmonella spp.

Abstract: Forty nine isolates were isolated from 34 food samples using Salmonella-Shigella medium, 10 of them were identified biochemically as Salmonella sp., two of them were multidrug-resistant, and they showed a resistance to seven tested antibiotics (ampicillin, streptomycin, gentamicin, nalidixic acid, ciprofloxacin, tetracycline, amoxicillin). Molecular identification of these isolates proved that they were Citrobacter ferundii and Proteus mirabilis. The antimicrobial activity for Lactobacillus acidophilus ATCC 43… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…However, the interaction between irradiation and food components directly could cause the development of undesirable sensory and chemical changes in some foods (Gliemmo, Latorre, Narvaiz, Campos, & Gerschenson, 2015). On the other hand, (Abdallah, Hussein, Khalil, Abdel-Aal, & El-Desokey, 2018) found that gamma irradiation could be used indirectly in food preservation by exposing the supernatant free cells of the probiotics bacteria (Lactic acid bacteria). As the antibacterial activity of the free cell supernatants of the Lactobacillus acidophilus and Streptococcus thermophilus increased by gamma radiation toward Salmonella typhi, Proteus mirabilis, and Citrobacter freundii more than the irradiated suspended LAB cells.…”
Section: Introductionmentioning
confidence: 99%
“…However, the interaction between irradiation and food components directly could cause the development of undesirable sensory and chemical changes in some foods (Gliemmo, Latorre, Narvaiz, Campos, & Gerschenson, 2015). On the other hand, (Abdallah, Hussein, Khalil, Abdel-Aal, & El-Desokey, 2018) found that gamma irradiation could be used indirectly in food preservation by exposing the supernatant free cells of the probiotics bacteria (Lactic acid bacteria). As the antibacterial activity of the free cell supernatants of the Lactobacillus acidophilus and Streptococcus thermophilus increased by gamma radiation toward Salmonella typhi, Proteus mirabilis, and Citrobacter freundii more than the irradiated suspended LAB cells.…”
Section: Introductionmentioning
confidence: 99%